HEIGHT INDICATORS OF PRIMARY SCHOOLCHILDREN IN THE CONDITIONS OF KARAKALPAKSTAN - Duysenbaeva, Biybiruza Ospanovna; Saparniyazov, Inomjan; Berdibaeva, Gulshat Sultamuratovna (SCIENCE and SOCIETY, 2026)
The article, the ecological significance of the environment and the hygienic significance of school equipment for the growth and development of younger schoolchildren, their height relative to the age of schoolchildren, as well as the correspondence of their body weight to the standard norm, were studied. The study was conducted in grades 1-4 of two schools located in the Chimbay district of the Republic of Karakalpakstan, where height indicators were determined and compared with the age of boys and girls. Data on the proportionality of students' height and body weight were discussed.
Keywords: ecological conditions; primary school age; height indicators; diet; vitamin and mineral-rich products